Advances in antiviral polysaccharides derived from edible and medicinal plants and mushrooms. (1st February 2020) - He, Xirui; Fang, Jiacheng; Guo, Qing; Wang, Ming; Li, Yongsheng; Meng, Yibin; Huang, Linhong
Highlights: PsEMPM inhibit the infection via interfering with a few steps in the virus life cycle. PsEMPM improve the host immune responses to accelerate the process of viral clearance. The antiviral potency of PsEMPM are determined by structural patterns. PsEMPM merit further investigation as promising antiviral agents. Abstract: Despite the number of approved antivirals has considerably increased, these existing drugs are not always efficacious or well-tolerated and drug-resistant virus strains are rapidly emerging. Nowadays, many polysaccharides as independent or the main bioactive ingredients have been approved as medicines. The present report aims to provide systematically reorganized information on antiviral polysaccharides derived from edible and medicinal plants and mushrooms (PsEMPM) to people for better utilization of them. PsEMPM can inhibit the infection of viruses by interfering with a few steps in the virus life cycle and/or improving the host antiviral immune responses. Polyanionic nature and sulfates are in many cases required antiviral potency of PsEMPM, while it not only is a function of high charge density but also associated with distinct structural speciﬁcities. Plenty of efforts have been devoted to achieving the discovery of novel antiviral polysaccharides, however, the detailed structural characteristics of PsEMPM still merit further in-depth investigation.